Active Expression of Human Hyaluronidase PH20 and Characterization of Its Hydrolysis Pattern - Pang, Bo; He, Jing; Zhang, Weijiao; Huang, Hao; Wang, Yang; Wang, Miao; Du, Guocheng; Kang, Zhen (Frontiers in Bioengineering and Biotechnology, 2022)
Hyaluronidases are a group of glycosidases catalyzing the degradation of hyaluronic acid (HA). Because the advantages of effectively hydrolyzing the HA-rich matrix and low immunogenicity, human hyaluronidase PH20 (hPH20) is widely used in medicine field. Here, we realized the active expression of recombinant hPH20 by Pichia pastoris under a methanol-induced promoter PAOX1. Through optimizing the composition of C-terminal domain and fusing protein tags, we constructed a fusion mutant AP2-△491C with the extracellular hyaluronidase activity of 258.1 U·L-1 in a 3-L bioreactor, the highest expression level of recombinant hPH20 produced by microbes. Furthermore, we found recombinant hPH20 hydrolyzed the β-1,4 glycosidic bonds sequentially from the reducing end of o-HAs with HA6NA as the smallest substrate. The result will provide important theoretical guidance for directed evolution of the enzyme to prepare multi-functional o-HAs with specific molecular weights.